Heat-Killed Lacticaseibacillus paracasei Ameliorated UVB-Induced Oxidative Damage and Photoaging and Its Underlying Mechanisms - Jing Xu; Xiaofang Zhang; Yan Song; Bin Zheng; Zhengshun Wen; Miao Gong; Lingting Meng (MDPI AG, 2022)
Ultraviolet B (UVB) radiation is a major environmental causative factor of skin oxidative damage and photoaging. Lacticaseibacillus paracasei is a well-known probiotic strain that can regulate skin health. The present study investigated the effects of heat-killed Lacticaseibacillus paracasei (PL) on UVB linked oxidative damage and photoaging in skin cells (Normal human dermal fibroblast (NHDF) cells and B16F10 murine melanoma cells). Results demonstrated that: (1) PL prevented UVB-induced cytotoxicity relating to decreased DNA damage in NHDF and B16F10 cells; (2) PL alleviated UVB-induced oxidative damage through increasing GSH content, as well as antioxidant enzyme activities and mRNA levels (except MnSOD activity and mRNA levels as well as CAT mRNA level) relating to the activation of Sirt1/PGC-1α/Nrf2 signaling in NHDF cells; (3) PL attenuated UVB-induced photoaging was noticed with a decrease in the percentage of SA-β-gal positive cells in NHDF cells model. Moreover, PL attenuated UVB-induced photoaging through exerting an anti-wrinkling effect by enhancing the type I collagen level relating to the inhibition (JNK, p38)/(c-Fos, c-Jun) of signaling in NHDF cells, and exerting an anti-melanogenic effect by suppressing tyrosinase and TYRP-1 activity and/or expressions relating to the inhibition of PKA/CREB/MITF signaling in B16F10 cells. In conclusion, PL could ameliorate UVB-induced oxidative damage and photoaging. Therefore, PL may be a potential antioxidant and anti-photoaging active ingredient for the cosmetic industry.